Teaching Vocabulary to Young Learners Using YouTube Videos at A Private School in Sumedang - Eva Meidi Kulsum; Rahma Sakina; Ervan Fauzan; Yustika Nur Fajriah (Ma'soem University, 2023)
This research focuses on learning vocabulary to young learners through YouTube videos and is categorized as descriptive-qualitative method using observation and interviews. This research was conducted at Al-Ma'soem Elementary School which involved 32 young learners and an English teacher. The results of this study were classified into 3 themes; the characteristics of YouTube videos, the advantages of using YouTube videos and the problems faced by teachers in using YouTube videos. It was found that all young learners at Al-Ma'soem Elementary School grade 1 were involved in learning vocabulary through YouTube videos. These young learners gave a positive response during the learning activities because they preferred learning English, especially learning vocabulary by using videos on YouTube. Related to the last findings, the lack of the teacher in preparing a suitable video and the unstable internet connection are considered as problems experienced by the teacher in using the videos on YouTube. Additionally, the use of YouTube videos to learn vocabulary in English learning is quite effective, however, the teachers are suggested to wisely choose the characteristics of videos that are suitable for young learners and find out the best solution to overcome the problems appeared.